2014 40th Annual Northeast Bioengineering Conference (NEBEC) 2014
DOI: 10.1109/nebec.2014.6972794
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle-embedded polymersome nanocarriers for the treatment of antibiotic-resistant infections

Abstract: Bacterial genetic resistance to antibiotics is a massive threat to global and US health care today. Infections caused by antibiotic-resistant bacteria are becoming increasingly prevalent and difficult to treat. This study explored the development and optimization of a polymersome nanocarrier formed from an amphiphilic diblock copolymer designed to overcome this resistance. Silver nanoparticles were embedded in the hydrophobic membrane of polymersomes while the antibiotic was encapsulated in the particle's aque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As an inspiring and pioneering discovery, Morones-Ramirez et al [11] recently found that Ag þ and antibiotic combinations could engender an obvious synergistic effect on killing the drug-resistant bacterial strains, thereby expanding the antibacterial spectrum of the existing antibiotic drugs. It seems that a drug delivery system that integrates silver and antibiotics would be a more promising therapy tool in this field [12]. However, a single-particle nanoplatform that could release Ag þ and antibiotics simultaneously has never been reported, as Ag þ in combination with antibiotics can not be directly administrated for clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…As an inspiring and pioneering discovery, Morones-Ramirez et al [11] recently found that Ag þ and antibiotic combinations could engender an obvious synergistic effect on killing the drug-resistant bacterial strains, thereby expanding the antibacterial spectrum of the existing antibiotic drugs. It seems that a drug delivery system that integrates silver and antibiotics would be a more promising therapy tool in this field [12]. However, a single-particle nanoplatform that could release Ag þ and antibiotics simultaneously has never been reported, as Ag þ in combination with antibiotics can not be directly administrated for clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of a fusion protein comprising of elastin-like peptides and KGF resulting into a self-assembled nanoparticle (chimeric nanoparticle) enhanced the reepithelialization and granulation, two crucial processes in wound healing [36]. To overcome bacterial antibiotic resistance, Geilich et al developed silver nanoparticles-embedded polymersomes [37]. This polymersome formulation constructed from a biodegradable diblock copolymer carrying silver nanoparticles embedded in the hydrophobic compartment and ampicillin in the hydrophilic compartment inhibited the growth of ampicillin-resistant Escherichia coli.…”
Section: Nanoparticles/micelles/lipidsmentioning
confidence: 99%
“…A new field has been established: nanoscience [1,2]. In view of this progress, there are NPs being obtained with a variety of metals, such as Ag, Au, Fe, Zn, Ti, and Si, among others [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature is plentiful regarding different strategies for NP synthesis and characterization [2,3,10], the establishment of the accurate content of the metal present in their structures is not receiving the same attention, and this important information is occasionally ignored completely. Once the real content of a metal in a NP is determined as being of the utmost importance, it is easy to rationalize that all of the results obtained from a study involving a NP are dependent on such information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation